KEBIJAKAN PEMERINTAH DAERAH PADA PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) - Virtha Dwi Oktavianny Lomboan; Lego Karjoko; M. Hudi Asrori S. (PROSEDING, 2022)
The Completed Systematic Land Registration Program (or PTSL) is a program of agrarian reform in the field of asset management which has a large positive influence in accelerating land registration. As for the obstacles in the implementation of the administration of land registration, such as the problem of paying taxes due to the economic capacity and conditions of certain communities who are unable to pay those costs. Based on Article 19 of the UUPA, the government shall carry out registration to uphold legal certainty in the land sector, considering that land is a very important object for various walks of life from various economic backgrounds and conditions. The purpose of writing this article is to find out what policies are given by the Regional Government to overcome this issue. This article used normative method. The approach method used are the law and library approach. The results found that from the Ministry of ATR/BPN has included (the solution) it in PERMEN ATR Nomor 06 tahun 2018, then there are some policies from several local governments from various regions that issue policies to reduce and even exempt costs that must be paid by the society. Keywords : PTSL, Land Administrative Registration , Government Policy.